A supercritical fluid foaming and hot pressing shaping process

Through supercritical fluid foaming and hot pressing shaping processes, combined with specific raw material ratios and process steps, the problem of insufficient performance of traditional sole materials is solved, and a midsole material with high rebound rate and wear resistance is prepared, suitable for sports midsole part of the shoe.

CN118700422BActive Publication Date: 2025-01-10DONGGUAN HAILEX HIGH POLYMER MATERIAL SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411047963.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2025-01-10
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

Traditional sole materials have shortcomings in meeting lightweight, high resilience and durability, and it is difficult to prepare midsole materials with high rebound rate, good compression permanent deformation performance, and excellent wear resistance.

Method used

Using supercritical fluid foaming and hot pressing shaping processes, the high rebound rate is prepared through specific raw material ratios and process steps, including intensive mixing, injection molding, vulcanization, wetting, foaming and hot pressing shaping, Compression of the midsole material with permanent deformation and wear resistance.

Benefits of technology

A midsole material with moderate hardness, high rebound rate, good compression permanent deformation performance and excellent wear resistance has been prepared, which is suitable for the midsole part of sports shoes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a process based on supercritical fluid foaming and hot pressing shaping, comprising the following steps: S1, adding all raw materials to a banbury mixer for mixing, and single-screw granulation to obtain composite material particles; S2, using an injection molding machine to inject and vulcanize the composite material particles to obtain a midsole embryo; S3, placing the midsole embryo in an autoclave for infiltration; S4, placing the infiltrated embryo in an oven for heating and foaming to obtain a semi-finished midsole; S5, placing the semi-finished midsole in a mold for hot pressing and shaping, and then cooling with water for 550 to 650 seconds to obtain a finished product. The present invention is simple to operate, and uses specific raw materials, proportions and processes. The obtained finished product not only has a high rebound rate and good compression permanent deformation performance, but also has excellent wear resistance and moderate hardness, and is very suitable for preparing midsole materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a supercritical fluid foaming and hot pressing shaping process. Background Art

[0002] Sports shoes are shoes designed for sports or travel. They are characterized by adapting to people's needs during activities. Compared with ordinary leather shoes or rubber shoes, the soles of sports shoes are softer and more elastic. This design can provide effective cushioning for the wearer. The sole structure of sports shoes is divided into three parts: outsole, midsole and insole.

[0003] With the rapid development of the sports shoe market, the requirements for the performance of sole materials are also increasing. Although traditional sole materials have certain cushioning properties, they are still insufficient in meeting the requirements of lightweight, high resilience and durability. In recent years, new sole materials based on supercritical fluid foaming and hot pressing shaping processes have gradually attracted attention and become a research hotspot in the field of sports shoe manufacturing. Therefore, how to use this technology and match it with a suitable raw material formula to prepare a midsole material with high rebound rate, good compression permanent deformation performance, excellent wear resistance and moderate hardness is still a major problem that needs to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide a supercritical fluid foaming and hot pressing shaping process. The present invention is simple to operate and uses specific raw materials, proportions and processes. The obtained finished product has not only high resilience and good compression permanent deformation performance, but also excellent wear resistance and moderate hardness, and is very suitable for preparing midsole materials.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A supercritical fluid foaming and hot pressing shaping process comprises the following steps:

[0007] S1, adding all raw materials into a banbury mixer and mixing, and single-screw granulation to obtain composite material particles;

[0008] S2, injection molding the composite material particles by an injection molding machine and vulcanizing them to obtain a midsole embryo;

[0009] S3, placing the midsole embryo into an autoclave for soaking;

[0010] S4, placing the soaked embryos in an oven to heat and foam, to obtain a semi-finished midsole;

[0011] S5. Place the semi-finished midsole into a mold, heat-press and shape it, and then cool it with water for 550-650 seconds to obtain a finished product.

[0012] In parts by weight, the raw materials include 20-30 parts of thermoplastic polyurethane elastomer, 40-60 parts of ethylene-vinyl acetate copolymer, 20-30 parts of polyolefin elastomer, 0.5-1.5 parts of lubricant, 0.1-0.5 parts of cross-linking agent, and 1-5 parts of reinforcing agent.

[0013] Preferably, the mass ratio of the thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer and polyolefin elastomer is 1:(1.5-2.5):(0.5-1.5); more preferably, it is 1:2:1.

[0014] Preferably, the thermoplastic polyurethane elastomer has a Shore hardness of 85A-95A and a specific gravity of 1.15-1.2 g / cm 3 , the tensile strength is 40~50MPa; further preferably, the Shore hardness of the thermoplastic polyurethane elastomer is 95A, the specific gravity is 1.18g / cm 3 , the tensile strength is 45MPa.

[0015] In some preferred embodiments, the thermoplastic polyurethane elastomer is purchased from Dongguan Dingyu New Materials Co., Ltd.

[0016] Preferably, the ethylene-vinyl acetate copolymer includes a first ethylene-vinyl acetate copolymer and a second ethylene-vinyl acetate copolymer.

[0017] Preferably, the mass ratio of the first ethylene-vinyl acetate copolymer to the second ethylene-vinyl acetate copolymer is (2-6):1; more preferably, it is 4:1.

[0018] Preferably, the melt index of the first ethylene-vinyl acetate copolymer at 190°C is 3-6 g / 10 min, and the vinyl acetate content is 22%-30%; further preferably, the melt index of the first ethylene-vinyl acetate copolymer at 190°C is 4 g / 10 min, and the vinyl acetate content is 26%.

[0019] In some preferred embodiments, the first ethylene-vinyl acetate copolymer is purchased from Taiwan Plastics Corporation in Taiwan Province, China, EVA 7470M.

[0020] Preferably, the melt index of the second ethylene-vinyl acetate copolymer at 190°C is 1-3 g / 10 min, and the vinyl acetate content is 15%-20%; further preferably, the melt index of the second ethylene-vinyl acetate copolymer at 190°C is 2.5 g / 10 min, and the vinyl acetate content is 18%.

[0021] In some preferred embodiments, the second ethylene-vinyl acetate copolymer is purchased from Taiwan Plastics Corporation in Taiwan Province, China, EVA SF45 TAISOX.

[0022] As one of the raw materials described in this process, ethylene-vinyl acetate copolymer can improve the flexibility and impact resistance of the prepared product, but the performance of ethylene-vinyl acetate copolymer will vary with the change of vinyl acetate content. The inventor found that when a specific ethylene-vinyl acetate copolymer is selected for compounding, and the mass ratio of the first ethylene-vinyl acetate copolymer to the second ethylene-vinyl acetate copolymer is (2~6):1, the prepared product can have good flexibility and impact resistance, as well as good hardness and wear resistance. This may be because, on the one hand, the molecular chains of ethylene-vinyl acetate copolymers with different vinyl acetate contents have different structures and properties. During the compounding process, these molecular chains will interact with each other to form a more complex network structure. This network structure can enhance the cohesion and stability of the material, thereby improving its comprehensive performance. On the other hand, by adjusting the ratio of ethylene-vinyl acetate copolymers with different vinyl acetate contents, the pore structure, pore size and distribution of the material can be controlled. These changes in microstructure will directly affect the density, hardness, resilience and other properties of the material. However, only two ethylene-vinyl acetate copolymers have limited improvement on product performance.

[0023] Preferably, the polyolefin elastomer includes a first polyolefin elastomer and a second polyolefin elastomer.

[0024] Preferably, the mass ratio of the first polyolefin elastomer to the second polyolefin elastomer is (2-6):1; more preferably, it is 4:1.

[0025] Preferably, the melt index of the first polyolefin elastomer at 190°C is 1-5g / 10min, the Mooney viscosity is 10-20MU, and the elongation at break is ≥800%; further preferably, the melt index of the first polyolefin elastomer at 190°C is 3.6g / 10min, the Mooney viscosity is 16MU, and the elongation at break is ≥1000%.

[0026] In some preferred embodiments, the first polyolefin elastomer is purchased from Mitsui Singapore, POE A-4070S.

[0027] Preferably, the melt index of the second polyolefin elastomer at 190°C is 25~40g / 10min, the Shore hardness is 65A~75A, and the melting temperature is 50~70°C; further preferably, the melt index of the second polyolefin elastomer at 190°C is 30g / 10min, the Shore hardness is 72A, and the melting temperature is 60°C.

[0028] In some preferred embodiments, the second polyolefin elastomer is purchased from Dow Chemical, USA, POE 8400.

[0029] The inventors found that the selection of a specific thermoplastic polyurethane elastomer and two polyolefin elastomers for blending and modification with ethylene-vinyl acetate copolymer, and the mass ratio of the thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, and polyolefin elastomer is 1: (1.5~2.5): (0.5~1.5) can improve the foaming ratio and wear resistance of the prepared product while also improving the rebound rate and compression permanent deformation performance of the product. This may be because the molecular faces of thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer, and polyolefin elastomer all contain specific functional groups and structures, so that they interact with each other during the blending process to form a strong intermolecular force, which helps to improve the stability of the product, making it less likely to be damaged when subjected to external forces, thereby improving the wear resistance, rebound rate, and compression permanent deformation performance of the material. By adjusting the ratio between the raw materials, a more uniform and dense cellular structure can be formed inside the material, which is helpful to obtain a material with a higher foaming ratio at high temperature. The cellular structure in this material can not only improve the impact resistance of the product, but also improve the comfort of the product, and it is more comfortable to apply it to the preparation of the midsole foot feel. In addition, the addition of a specific second polyolefin elastomer can improve the processing properties such as the fluidity, plasticity and formability of the product, and promote the uniform dispersion of raw materials such as crosslinking agents and lubricants. However, the ratio between these raw materials needs to be strictly controlled, because although the thermoplastic polyurethane elastomer improves the overall performance of the product, since the present invention is carried out under supercritical conditions, the excessive thermoplastic polyurethane elastomer has a certain hindering effect on the diffusion of the blowing agent carbon dioxide and nitrogen mixed gas, which will cause the pore size to be reduced and the foaming efficiency to be reduced. And the polyolefin elastomer is excessive, and its soft non-polar segment will not only cause the hardness to drop too fast, but also cause the reinforcing agent modified hollow glass microspheres in the present invention to be unevenly dispersed in the system, thereby causing the aggregation of bubbles and uneven pores, affecting the performance of the product such as the foaming ratio, resilience and wear resistance.

[0030] Preferably, the lubricant is stearic acid and oxidized polyethylene wax.

[0031] Preferably, the mass ratio of stearic acid to oxidized polyethylene wax is (1-3):1, and more preferably, 2:1.

[0032] Preferably, the kinematic viscosity of the oxidized polyethylene wax at 140°C is 15-25 mm 2 / s, and a softening point of 110-120°C; further preferably, the kinematic viscosity of the oxidized polyethylene wax at 140°C is 20.5 mm 2 / s, softening point is 115℃.

[0033] In some preferred embodiments, the oxidized polyethylene wax is purchased from Henan Yuyang Wax Co., Ltd.

[0034] Preferably, the cross-linking agent is one or more of di-tert-butyl diisopropylbenzene peroxide and diisopropylbenzene peroxide; further preferably, it is di-tert-butyl diisopropylbenzene peroxide.

[0035] Preferably, the reinforcing agent is modified hollow glass microspheres.

[0036] The preparation method of the modified hollow glass microspheres comprises the following steps:

[0037] A1, using coupling agent to modify hollow glass microspheres;

[0038] A2, using isocyanate to modify graphene oxide;

[0039] A3. Mix the products obtained in step A1 and step A2, disperse them in N,N-dimethylformamide, stir them at 80-100° C. for 20-30 h, filter and dry them.

[0040] Preferably, the coupling agent is one or more of KH550, KH560, KH570, KH590, and KH792; more preferably, it is KH550 and KH590.

[0041] Preferably, the mass ratio of KH550 to KH590 is 1:(5-7); more preferably, it is 1:6.

[0042] Preferably, the average particle size of the hollow glass microspheres is 20-50 μm, the particle size distribution range is 5-100 μm, and the compressive strength is ≥30 MPa; further preferably, the average particle size of the hollow glass microspheres is 35 μm, the particle size distribution range is 10-80 μm, and the compressive strength is ≥30 MPa.

[0043] In some preferred embodiments, the hollow glass microspheres are purchased from Wenzhou Weizhen New Materials Co., Ltd.

[0044] Preferably, the added amount of the coupling agent is 2% to 8% of the mass of the hollow glass microspheres.

[0045] As a common reinforcing agent, hollow glass microspheres can improve the foaming ratio and compression permanent deformation performance of foaming materials to a certain extent, and have little effect on product density. However, the compatibility between hollow glass microspheres and elastomer raw materials is poor, which affects its role in the system. The inventors found that by modifying the hollow glass microspheres with two coupling agents, their dispersibility in the system can be improved. This may be because the surface of the hollow glass microspheres is modified and grafted with coupling agent functional groups such as amino and thiol, which can react with the active groups in the elastomer, thereby producing stronger interactions, improving the interface bonding between the elastomer and the hollow glass microspheres, and improving the compatibility between the hollow glass microspheres and the elastomer, thereby improving the product's rebound rate, foaming ratio and compression permanent deformation and other properties. However, the volume required for hollow glass microspheres is large, and the efficiency of improving product performance is low.

[0046] The specific method of modifying the hollow glass microspheres is: taking the coupling agent and hydrolyzing it in an ethanol aqueous solution with a concentration of 80wt / %, then adding the hollow glass microspheres, stirring at 55-65°C for 2-4h, filtering, and drying at 100°C for 12h to obtain the product.

[0047] Preferably, the volume ratio of the coupling agent to the ethanol aqueous solution is 1:30-50; more preferably, it is 1:40.

[0048] Preferably, the isocyanate is one or more of 4,4'-methylenebis(phenyl isocyanate), tert-butyl isocyanate, ethyl isocyanate, and p-phenylene diisocyanate; more preferably, it is 4,4'-methylenebis(phenyl isocyanate).

[0049] Preferably, the graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide.

[0050] Preferably, the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:(0.5-2); further preferably, it is 2:3.

[0051] Preferably, the average thickness of the single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm.

[0052] Preferably, the multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.

[0053] In some preferred embodiments, the single-layer graphene oxide and the multi-layer graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0054] The specific method of modifying the graphene oxide is: taking the graphene oxide and dispersing it evenly in N,N-dimethylformamide, then adding isocyanate, stirring at 80-100° C. for 30-40 hours, filtering and drying to obtain the modified graphene oxide.

[0055] Preferably, the solid-to-liquid ratio of the graphene oxide and N,N-dimethylformamide is 1 g:15-25 mL; further preferably, it is 1 g:20 mL.

[0056] Preferably, in step A3, the mass ratio of the products of step A1 and step A2 is (8-12):1.

[0057] The inventors found that by selecting two specific graphene oxides and compounding with hollow glass microspheres, the hardness, rebound rate, foaming ratio and compression permanent deformation of the product can be further improved. This may be because on the one hand, by selecting specific single-layer graphene oxide and multi-layer graphene oxide, they have similar diameters and little difference in thickness, so there is a certain compatibility between the two. On the one hand, the complementarity in the number of layers is achieved, which not only retains the high activity of the single-layer graphene oxide, but also improves the mechanical properties of the product. On the other hand, the single-layer and multi-layer graphene oxides of similar sizes are intertwined and stacked to form a stable three-dimensional network structure, which can improve the structural stability of the final prepared product, thereby improving the rebound rate and compression permanent deformation performance of the product. However, the particle size of graphene oxide is too small and has poor dispersibility in the system. The inventors found that by grafting graphene oxide on the surface of hollow glass microspheres, the prepared synergistic reinforcing agent modified hollow glass microspheres can greatly improve product performance. This may be because the hollow glass microspheres not only serve as a reinforcing agent to improve product performance, but also as a carrier of graphene oxide, allowing graphene oxide to be evenly dispersed on the surface of the hollow glass microspheres and thus evenly dispersed in the system, achieving the effect of further improving product performance. However, excessive graphene oxide will still agglomerate.

[0058] Preferably, the solid-to-liquid ratio of the product obtained in step A1 and step A2 to N,N-dimethylformamide is 1 g:15-25 mL; more preferably, it is 1 g:20 mL.

[0059] Preferably, the specific conditions of the banburying mixing in step S1 are: a discharge temperature of 120-130° C., and a die head temperature of 110-120° C.

[0060] Preferably, during the injection molding in step S2, the material tube is divided into four sections, the temperature of the first section of the material tube is 85~95°C, the temperature of the second section of the material tube is 85~95°C, the temperature of the third section of the material tube is 85~90°C, the temperature of the fourth section of the material tube is 85~90°C, the mold temperature is 170~175°C, and the vulcanization time is 450~500s.

[0061] Preferably, the infiltration conditions in step S3 are: infiltration temperature 125-135° C., infiltration pressure 13-18 MPa, and infiltration time 2-4 h.

[0062] Preferably, the temperature-raising foaming conditions in step S4 are as follows: the foaming agent is a mixed gas of carbon dioxide and nitrogen, the foaming temperature is 140-150° C., and the foaming time is 10-30 min.

[0063] Preferably, in the carbon dioxide and nitrogen mixed gas, the volume ratio of carbon dioxide to nitrogen is (3-6):1; more preferably, it is 5:1.

[0064] Preferably, the hot pressing and shaping conditions in step S5 are: temperature 165-175° C., hot pressing time 550-650 s.

[0065] The present invention also includes products prepared by the supercritical fluid foaming and hot pressing shaping process.

[0066] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0067] 1. The present invention provides a supercritical fluid foaming and hot pressing shaping process, which is simple to operate and uses specific raw materials, proportions and processes. The obtained finished product has not only high resilience and good compression permanent deformation performance, but also excellent wear resistance and moderate hardness, and is very suitable for preparing midsole materials.

[0068] 2. The present invention selects a specific ethylene-vinyl acetate copolymer for compounding, and when the mass ratio of the first ethylene-vinyl acetate copolymer to the second ethylene-vinyl acetate copolymer is (2-6):1, the prepared product can have good flexibility and impact resistance as well as good hardness and wear resistance.

[0069] 3. The present invention selects a specific thermoplastic polyurethane elastomer and two polyolefin elastomers to be blended and modified with ethylene-vinyl acetate copolymer, and the mass ratio of the thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer and polyolefin elastomer is 1: (1.5-2.5): (0.5-1.5). While improving the foaming ratio and wear resistance of the prepared product, the rebound rate and compression permanent deformation performance of the product can also be improved.

[0070] 4. The present invention can improve the dispersibility of hollow glass microspheres in the system by selecting two coupling agents to modify the hollow glass microspheres.

[0071] 5. The present invention can further improve the hardness, resilience, expansion ratio and compression permanent deformation of the product by selecting two specific graphene oxides and compounding them with hollow glass microspheres. DETAILED DESCRIPTION

[0072] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0073] The raw materials used in the present invention are all commercially available, specifically:

[0074] Thermoplastic polyurethane elastomer, Shore hardness 95A, specific gravity 1.18g / cm 3 , tensile strength is 45MPa, purchased from Dongguan Dingyu New Materials Co., Ltd.

[0075] The first ethylene-vinyl acetate copolymer has a melt index of 4 g / 10 min at 190° C. and a vinyl acetate content of 26%, and is purchased from Taiwan Plastics, Taiwan Province, China, EVA 7470M.

[0076] The second ethylene-vinyl acetate copolymer has a melt index of 2.5 g / 10 min at 190° C. and a vinyl acetate content of 18%, and is purchased from Taiwan Plastics, Taiwan Province, China, EVA SF45 TAISOX.

[0077] The first polyolefin elastomer has a melt index of 3.6 g / 10 min at 190° C., a Mooney viscosity of 16 MU, and an elongation at break of ≥1000%, and is purchased from Mitsui Singapore, POE A-4070S.

[0078] The second polyolefin elastomer has a melt index of 30 g / 10 min at 190° C., a Shore hardness of 72A, and a melting temperature of 60° C. and is purchased from Dow Chemical, USA, and is POE 8400.

[0079] Oxidized polyethylene wax, kinematic viscosity at 140°C is 20.5 mm 2 / s, softening point is 115℃, purchased from Henan Yuyang Wax Industry Co., Ltd.

[0080] Hollow glass microspheres with an average particle size of 35 μm, a particle size distribution range of 10-80 μm, and a compressive strength of ≥30 MPa were purchased from Wenzhou Weizhen New Materials Co., Ltd.

[0081] The average thickness of single-layer graphene oxide is 0.5~1.2nm, and the diameter is 4~7μm; the average thickness of multi-layer graphene oxide is 1~3nm, the diameter is 4~7μm, and the number of layers is 2~5; both were purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0082] Example 1

[0083] This embodiment provides a supercritical fluid foaming and hot pressing shaping process, the steps of which are:

[0084] S1, adding all raw materials into a banbury mixer and mixing, and single-screw granulation to obtain composite material particles;

[0085] S2, injection molding the composite material particles by an injection molding machine and vulcanizing them to obtain a midsole embryo;

[0086] S3, placing the midsole embryo into an autoclave for soaking;

[0087] S4, placing the soaked embryos in an oven to heat and foam, to obtain a semi-finished midsole;

[0088] S5. Place the semi-finished midsole into a mold, heat-press and shape it, and then cool it with water for 600 seconds to obtain a finished product.

[0089] In parts by weight, the raw materials include 25 parts of thermoplastic polyurethane elastomer, 50 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 0.8 parts of lubricant, 0.25 parts of cross-linking agent, and 3 parts of reinforcing agent.

[0090] The ethylene-vinyl acetate copolymer is a first ethylene-vinyl acetate copolymer and a second ethylene-vinyl acetate copolymer.

[0091] The mass ratio of the first ethylene-vinyl acetate copolymer to the second ethylene-vinyl acetate copolymer is 4:1.

[0092] The polyolefin elastomer is a first polyolefin elastomer and a second polyolefin elastomer.

[0093] The mass ratio of the first polyolefin elastomer to the second polyolefin elastomer is 4:1.

[0094] The lubricants are stearic acid and oxidized polyethylene wax.

[0095] The mass ratio of the stearic acid to the oxidized polyethylene wax is 2:1.

[0096] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0097] The reinforcing agent is modified hollow glass microspheres.

[0098] The preparation method of the modified hollow glass microspheres comprises the following steps:

[0099] A1, using coupling agent to modify hollow glass microspheres;

[0100] A2, using isocyanate to modify graphene oxide;

[0101] A3. Mix the products obtained in step A1 and step A2, disperse them in N,N-dimethylformamide, stir them at 90° C. for 25 h, filter and dry them.

[0102] The coupling agents are KH550 and KH590.

[0103] The mass ratio of KH550 to KH590 is 1:6.

[0104] The added amount of the coupling agent is 5% of the mass of the hollow glass microspheres.

[0105] The specific method of modifying the hollow glass microspheres is: taking the coupling agent and hydrolyzing it in an ethanol aqueous solution with a concentration of 80wt / %, then adding the hollow glass microspheres, stirring at 60°C for 3h, filtering, and drying at 100°C for 12h to obtain the product.

[0106] The volume ratio of the coupling agent to the ethanol aqueous solution is 1:40.

[0107] The isocyanate is 4,4'-methylenebis(phenyl isocyanate).

[0108] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide.

[0109] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 2:3.

[0110] The specific method of modifying the graphene oxide is: taking the graphene oxide and dispersing it evenly in N,N-dimethylformamide, then adding isocyanate, stirring at 90° C. for 35 hours, filtering and drying to obtain the modified graphene oxide.

[0111] The solid-to-liquid ratio of the graphene oxide and N,N-dimethylformamide is 1 g:20 mL.

[0112] In the step A3, the mass ratio of the products of step A1 and step A2 is 10:1.

[0113] The solid-to-liquid ratio of the product obtained in step A1 and step A2 to N,N-dimethylformamide is 1 g:20 mL.

[0114] The specific conditions of the internal mixing in step S1 are: a discharge temperature of 125° C. and a die head temperature of 115° C.

[0115] During the injection molding in step S2, the material tube is divided into four sections, the temperature of the first section of the material tube is 90°C, the temperature of the second section of the material tube is 90°C, the temperature of the third section of the material tube is 87°C, the temperature of the fourth section of the material tube is 87°C, the mold temperature is 173°C, and the vulcanization time is 480s.

[0116] The infiltration conditions in step S3 are: infiltration temperature 130° C., infiltration pressure 16 MPa, and infiltration time 3 h.

[0117] The heating and foaming conditions in step S4 are as follows: the foaming agent is a mixed gas of carbon dioxide and nitrogen, the foaming temperature is 145° C., and the foaming time is 20 min.

[0118] In the carbon dioxide and nitrogen mixed gas, the volume ratio of carbon dioxide to nitrogen is 5:1.

[0119] The hot pressing and shaping conditions in step S5 are: temperature 170° C., hot pressing time 600 s.

[0120] Example 2

[0121] The difference between this embodiment and embodiment 1 is that, in parts by weight, the raw materials include 30 parts of thermoplastic polyurethane elastomer, 50 parts of ethylene-vinyl acetate copolymer, 30 parts of polyolefin elastomer, 1 part of lubricant, 0.25 parts of cross-linking agent, and 3 parts of reinforcing agent.

[0122] Example 3

[0123] The difference between this embodiment and Embodiment 1 is that the mass ratio of the first polyolefin elastomer to the second polyolefin elastomer is 5:1.

[0124] Comparative Example 1

[0125] The difference between this comparative example and Example 1 is that, by weight, the raw materials include 25 parts of thermoplastic polyurethane elastomer, 70 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 0.8 parts of lubricant, 0.25 parts of cross-linking agent, and 3 parts of reinforcing agent.

[0126] Comparative Example 2

[0127] The difference between this comparative example and Example 1 is that, by weight, the raw materials include 40 parts of thermoplastic polyurethane elastomer, 50 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 0.8 parts of lubricant, 0.25 parts of cross-linking agent, and 3 parts of reinforcing agent.

[0128] Comparative Example 3

[0129] The difference between this comparative example and Example 1 is that, by weight, the raw materials include 25 parts of thermoplastic polyurethane elastomer, 50 parts of ethylene-vinyl acetate copolymer, 40 parts of polyolefin elastomer, 0.8 parts of lubricant, 0.25 parts of cross-linking agent, and 3 parts of reinforcing agent.

[0130] Comparative Example 4

[0131] The difference between this comparative example and Example 1 is that the mass ratio of the first ethylene-vinyl acetate copolymer to the second ethylene-vinyl acetate copolymer is 1:1.

[0132] Comparative Example 5

[0133] The difference between this comparative example and Example 1 is that the polyolefin elastomer is the first polyolefin elastomer.

[0134] Comparative Example 6

[0135] The difference between this comparative example and Example 1 is that the preparation method of the modified hollow glass microspheres comprises the steps of modifying the hollow glass microspheres only by using a coupling agent.

[0136] Comparative Example 7

[0137] The difference between this comparative example and Example 1 is that the graphene oxide is a single-layer graphene oxide.

[0138] Comparative Example 8

[0139] The difference between this comparative example and Example 1 is that the mass ratio of the products of step A1 and step A2 in step A3 is 6:1.

[0140] Comparative Example 9

[0141] The difference between this comparative example and Example 1 is that the thermoplastic polyurethane elastomer has a Shore hardness of 60A and a specific gravity of 1.1 g / cm 3 , tensile strength is 13MPa, purchased from Dongguan Dingyu New Materials Co., Ltd.

[0142] Performance Testing

[0143] Hardness test: refer to HG / T 2489-2007 "Hardness test method for microporous materials for shoes". Rebound rate test: refer to GB / T 10652-2001 "Determination of elasticity of porous polymer elastic materials". Compression permanent deformation test: refer to HG / T 2876-2009 "Compression deformation test method for microporous materials for rubber and plastic shoes". Wear resistance test: refer to GB / T9867-2008 "Determination of rubber resistance" to get the wear amount. The results are shown in Table 1.

[0144] Table 1 Measurement results

[0145]

[0146] According to statistics, the products prepared by supercritical fluid foaming and hot pressing shaping process in Examples 1 to 3 of the present invention have moderate hardness, high resilience, small compression permanent deformation and excellent wear resistance. In Comparative Example 1, the amount of ethylene-vinyl acetate copolymer added is too high, in Comparative Example 2, the amount of thermoplastic polyurethane elastomer added is too high, in Comparative Example 3, the amount of polyolefin elastomer added is too high, in Comparative Example 4, the mass ratio of the two ethylene-vinyl acetate copolymers is not within the scope of this application, in Comparative Example 5, no second polyolefin elastomer is added, in Comparative Example 6, no graphene oxide is added, in Comparative Example 7, no multilayer graphene oxide is added, in Comparative Example 8, the amount of graphene oxide added is too high, and in Comparative Example 9, the thermoplastic polyurethane elastomer has low hardness, specific gravity, and tensile strength. The hardness, rebound rate, compression permanent deformation, and wear resistance of the prepared product do not fully meet the requirements. Therefore, the supercritical fluid foaming and hot pressing shaping process described in this application is adopted, which is simple to operate, and specific raw materials, proportions, and processes are selected. The finished product not only has high rebound rate and good compression permanent deformation performance, but also excellent wear resistance and moderate hardness, and is very suitable for preparing midsole materials.

[0147] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A supercritical fluid foaming and hot pressing shaping process, characterized in that: The following steps are involved: S1, adding all raw materials into a banbury mixer and mixing, and single-screw granulation to obtain composite material particles; S2, injection molding the composite material particles by an injection molding machine and vulcanizing them to obtain a midsole embryo; S3, placing the midsole embryo into an autoclave for soaking; S4, placing the soaked embryos in an oven to heat and foam, to obtain a semi-finished midsole; S5, placing the semi-finished midsole into a mold, hot pressing and shaping, and then cooling with water for 550-650 seconds to obtain a finished product; In parts by weight, the raw materials include 20-30 parts of thermoplastic polyurethane elastomer, 40-60 parts of ethylene-vinyl acetate copolymer, 20-30 parts of polyolefin elastomer, 0.5-1.5 parts of lubricant, 0.1-0.5 parts of cross-linking agent, and 1-5 parts of reinforcing agent; The mass ratio of the thermoplastic polyurethane elastomer, ethylene-vinyl acetate copolymer and polyolefin elastomer is 1: (1.5-2.5): (0.5-1.5); The thermoplastic polyurethane elastomer has a Shore hardness of 85A-95A and a specific gravity of 1.15-1.2 g / cm 3 , tensile strength is 40~50MPa; The ethylene-vinyl acetate copolymer comprises a first ethylene-vinyl acetate copolymer and a second ethylene-vinyl acetate copolymer; the mass ratio of the first ethylene-vinyl acetate copolymer to the second ethylene-vinyl acetate copolymer is (2-6):1; the first ethylene-vinyl acetate copolymer has a melt index of 3-6 g / 10 min at 190° C., and a vinyl acetate content of 22%-30%; the second ethylene-vinyl acetate copolymer has a melt index of 1-3 g / 10 min at 190° C., and a vinyl acetate content of 15%-20%; The polyolefin elastomer comprises a first polyolefin elastomer and a second polyolefin elastomer; the mass ratio of the first polyolefin elastomer to the second polyolefin elastomer is (2-6):1; the first polyolefin elastomer has a melt index of 1-5 g / 10 min at 190° C., a Mooney viscosity of 10-20 MU, and an elongation at break of ≥800%; the second polyolefin elastomer has a melt index of 25-40 g / 10 min at 190° C., a Shore hardness of 65A-75A, and a melting temperature of 50-70° C.; The reinforcing agent is a modified hollow glass microsphere, and the preparation method comprises the following steps: A1, using coupling agent to modify hollow glass microspheres; A2, using isocyanate to modify graphene oxide; A3, the products obtained in step A1 and step A2 are mixed and dispersed in N,N-dimethylformamide, stirred at 80-100°C for 20-30h, filtered and dried to obtain; The hollow glass microspheres have an average particle size of 20-50 μm, a particle size distribution range of 5-100 μm, and a compressive strength of ≥30 MPa; The graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide; the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:(0.5-2); the average thickness of the single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of the multi-layer graphene oxide is 1-3 nm, the diameter is 4-7 μm, and the number of layers is 2-5.

2. The supercritical fluid foaming and hot pressing shaping process according to claim 1, characterized in that: The lubricants are stearic acid and oxidized polyethylene wax.

3. The supercritical fluid foaming and hot pressing shaping process according to claim 1, characterized in that: The cross-linking agent is one or more of di-tert-butyl diisopropylbenzene peroxide and diisopropylbenzene peroxide.

4. The supercritical fluid foaming and hot pressing shaping process according to claim 1, characterized in that: The heating and foaming conditions in step S4 are as follows: the foaming agent is a mixture of carbon dioxide and nitrogen, the foaming temperature is 140-150° C., and the foaming time is 10-30 min.

5. The supercritical fluid foaming and hot pressing shaping process according to claim 4, characterized in that: In the carbon dioxide and nitrogen mixed gas, the volume ratio of carbon dioxide to nitrogen is (3-6):

1.

6. A product prepared by the supercritical fluid foaming and hot pressing shaping process according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Thermoplastic resin foam and process for producing the same

    CN101679666A

  • Thermoplastic polyurethane elastomer and preparation method, application and product thereof

    CN106674471A